PANDANGAN DUNIA PENGARANG DAN RELASI KEKUASAAN DALAM NOVEL MAX HAVELAAR KARYA MULTATULI: KAJIAN STRUKTURALISME GENETIK - Herning Puspitarini; Sri Wahyuningtyas (Smart Education, 2025)
Abstract: Max Havelaar is a novel that considered “murder” of colonialism. As a historical novel, its expressed criticism of the colonial era so Max Havelaar is regarded as canon. The formulation of the problem are 1) how the existence of the problematic hero in the Max Havelaar novel based on the background social life author? 2) how historical background that influence the creation of the novel Max Havelaar and relationship with the power relations in the novel? 3) what a world view are successfully expressed through the resolution of the problem by problematic hero in the Max Havelaar novel? To solve the problem the authors use research methods of Sociology of literature with the theory of genetic structuralism. The results of the analysis show the social backgrounds of the author's influence on the formation of the problematic hero and the oposition, and there are power relations that connect hero problematic on the background of the history of the creation of the novel, so that determine the views of the world the author of the idealistic-humanist and liberalism from the collective subject who described through the dialectic method of understanding-explanations. Keyword: structuralism genetic, a world view, problematic hero, power relations Abstrak: Max Havelaar merupakan novel yang dianggap “membunuh” kolonialisme. Sebagai novel sejarah yang mengungkapkan kritik terhadap kolonial Max Havelaar dianggap sebagai karya agung. Rumusan masalah yang diambil yakni 1) bagaimanakah eksistensi tokoh problematik yang terdapat dalam novel Max Havelaar berdasarkan latar kehidupan sosial pengarang? 2) bagaimanakah latar belakang sejarah yang berpengaruh terhadap pembuatan novel Max Havelaar dan hubungannya dengan relasi kekuasaan yang terdapat dalam novel? 3) pandangan dunia seperti apa yang berhasil diungkapkan melalui penyelesaian masalah oleh tokoh problematik dalam novel Max Havelaar? Untuk memecahkan masalah tersebut penulis menggunakan metode penelitian sosiologi sastra dengan teori strukturalisme genetik. Hasil analisis menunjukkan latar belakang sosial pengarang berpengaruh terhadap pembentukan karakter tokoh problematik dengan oposisinya, serta terdapat relasi kekuasaan yang menghubungkan tokoh problematik berdasarkan latar belakang sejarah pembuatan novel, sehingga menentukan pandangan dunia pengarang yang idealis-humanis dan liberalisme dari subjek kolektifnya yang dijelaskan melalui metode dialektika pemahaman-penjelasan. Kata kunci: Strukturalisme genetik, pandangan dunia, tokoh problematik, relasi kekuasaan